2013
DOI: 10.4248/br201304002
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Blood Flow in Bone Repair and Maintenance

Abstract: Bone is a highly vascularized tissue, although this aspect of bone is often overlooked. In this article, the importance of blood flow in bone repair and regeneration will be reviewed. First, the skeletal vascular anatomy, with an emphasis on long bones, the distinct mechanisms for vascularizing bone tissue, and methods for remodeling existing vasculature are discussed. Next, techniques for quantifying bone blood flow are briefly summarized. Finally, the body of experimental work that demonstrates the role of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
181
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(189 citation statements)
references
References 127 publications
3
181
0
5
Order By: Relevance
“…53 Although the exact permissible motion value for UHMWPE is still unknown, it was suggested that the orderly anchoring collagen I fibers binded graft strongly to bones such that there was minimal movement between the implant and host tissue. In contrast, although there was no new bone formation, VEGF promoted the angiogenesis so that the vascular networks support the metabolic demands of repair and the influx of cells providing osteogenic cues, 54 which is adverse to the activity of osteoclasts. 55 The graft choice for ACL reconstruction is the focus of attention in sports medicine.…”
mentioning
confidence: 98%
“…53 Although the exact permissible motion value for UHMWPE is still unknown, it was suggested that the orderly anchoring collagen I fibers binded graft strongly to bones such that there was minimal movement between the implant and host tissue. In contrast, although there was no new bone formation, VEGF promoted the angiogenesis so that the vascular networks support the metabolic demands of repair and the influx of cells providing osteogenic cues, 54 which is adverse to the activity of osteoclasts. 55 The graft choice for ACL reconstruction is the focus of attention in sports medicine.…”
mentioning
confidence: 98%
“…Allografts, however, result in 60% 10-year post-implantation failure rates due to poor integration and remodeling into host tissue, which is due in part to poor vascularization [3][4][5]. Blood flow is important for multiple phases in bone healing since blood vessels deliver oxygen, nutrients, growth factors, and circulating cells to the graft sites [6]. However, skeletal blood flow has not been widely studied due to limitations with existing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, skeletal blood flow has not been widely studied due to limitations with existing techniques. Labeled microsphere administration is generally considered the gold standard technique for blood flow quantification, but is regarded as experimentally difficult and requires sacrifice of animals [6]. Laser Doppler imaging is a non-invasive technique to measure two-dimensional blood flow, but is limited due to shallow penetration depths [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that angiogenesis is stimulated in response to bone injury, resulting in increased transportation of osteoprogenitor cells and increased bone formation, whereas bone disuse leads to a reduction of the blood supply, resulting in decreased bone mass. 9) Evaluating intraosseous vascularization with regard to bone microstructure is important for treatments aimed at the recovery of bone tissue anisotropy and also the development of biomedical materials to induce oriented bone tissue regeneration. Nevertheless, even the evaluation methods for intraosseous vascular structure are not well established.…”
Section: Introductionmentioning
confidence: 99%
“…4,9) In addition to the bone matrix consisting of collagen brils and BAp, osteocyte networks are also an interacting element for the vascular patterns, because osteocyte networks have direct connections to vasculatures, enabling the transportation of molecules to and from osteocytes throughout the body. 25) Osteocytes are known to act as a mechanosensor in bone tissue and transmit biomechanical signals to osteoclasts/osteoblasts through uid ow inside the osteocyte networks.…”
mentioning
confidence: 99%